For this case we can write the following linear expressions:
We now subtract both linear expressions:
From here, we must subtract similar terms.
We have then:
Rewriting we have:
That is, we obtain the desired result.
Answer:
2 linear expressions whose difference is 5x-4 is:
Answer:
x=0
Step-by-step explanation:
9x-7=-7
Add 7 to each side
9x-7+7=-7+7
9x = 0
Divide each side by 9
9x/9 = 0/9
x = 0
6N + 12N = 40
6N + 12 = 40
6(N + 12) = 40
first blank
y-0=-3/5(x-3)
3y=-5(x-3)
y-3=3/5(x-0)
second blank
y=-9/5x+3/5
5y=-3(x-3)
y=-3/5x+9/5